A new confidence region for the multinomial distribution. Issue 5 (28th May 2017) - Withers, Christopher S.; Nadarajah, Saralees
ABSTRACT: A simple confidence region is proposed for the multinomial parameter. It is designed for situations having zero cell counts. Simulation studies as well as a real data application show that it performs at least as well as than at least two of the most common confidence regions.